ChemInform Abstract: A Stable Microporous Mixed‐Metal Metal—Organic Framework with Highly Active Cu2+ Sites for Efficient Cross‐Dehydrogenative Coupling Reactions. Issue 31 (5th August 2014) - Yang, Xiu‐Li; Zou, Chao; He, Yabing; Zhao, Min; Chen, Banglin; Xiang, Shengchang; O'Keeffe, Michael; Wu, Chuan‐De
Abstract The syntheses of the nanotubular Mn/Cu‐catalyst MOF as well as a Ni/Mn‐analogue containing nanopore cages are described.